Comprehensive analyses of PDHA1 that serves as a predictive biomarker for immunotherapy response in cancer - Deng, Langmei; Jiang, Anqi; Zeng, Hanqing; Peng, Xiaoji; Song, Liying (Frontiers in Pharmacology, 2022)
Recent studies have proposed that pyruvate dehydrogenase E1 component subunit alpha (PDHA1), a cuproptosis-key gene, are crucial to glucose metabolism reprogram of tumor cells. However, the functional roles and regulated mechanisms of PDHA1 in multiple cancers are largely unknown. The Cancer Genome Atlas (TCGA), GEPIA2 and cBioPortal were utilized to elucidate the function of PDHA1 in 33 tumor types. We found that PDHA1 was aberrantly expressed in most cancer types. Lung adenocarcinoma (LUAD) patients with high PDHA1 level were significantly correlated with poor prognosis of overall survival (OS) and first progression (FP). Kidney renal clear cell carcinoma (KIRC) patients with low PDHA1 level displayed poor OS and disease-free survival (DFS). However, for stomach adenocarcinoma (STAD), down-regulated PDHA1 expression predicted good prognosis in patients. Additionally, we evaluated the mutation diversity of PDHA1 in cancers and their association with prognosis. We also analyzed the protein phosphorylation and DNA methylation of PDHA1 in various tumors. PDHA1 expression was negatively correlated with tumor-infiltrating immune cells, such as myeloid dendritic cells (DC), B cells, and T cells in pan-cancers. Mechanically, we used single cell sequencing to discover that PDHA1 expression had a close link with several cancer-associated signaling pathways, such as DNA damage, cell invasion and angiogenesis. At last, we conducted a co‑expressed enrichment analysis and showed that aberrantly expressed PDHA1 participated in the regulation of mitochondrial signaling pathways, including oxidative phosphorylation, cellular respiration and electron transfer activity. In summary, PDHA1 could be a prognostic and immune-associated biomarker in multiple cancers.